Quantitative structure-reactivity relationships for pyrolysis and gasification of torrefied xylan. (1st December 2019) - Fan, Yuyang; Li, Luwei; Tippayawong, Nakorn; Xia, Shengpeng; Cao, Fengzhu; Yang, Xingwei; Zheng, Anqing; Zhao, Zengli; Li, Haibin
Abstract: Hemicellulose is the most reactive component of biomass during torrefaction. Torrefied hemicellulose will be one of the most significant factors determining the reactivity of torrefied biomass during subsequent pyrolysis and CO2 gasification. Xylan, as the representative for hemicellulose, was torrefied in a bench scale tubular reactor with varying torrefaction temperature and residence time. The results demonstrated that the pyrolysis and CO2 gasification reactivity of xylan and its derived char was evidently reduced by torrefaction. As torrefaction temperature increased from 200 to 280 °C, the comprehensive pyrolysis index (CPI) of xylan decreased evidently from 16.14 to 2.72 10 -4 %/(min·°C 2 ), while the average CO2 gasification reactivity of biochar derived from xylan decreased from 9.11 to 7.33 min −1 . These results could be attributed to that xylan proceeded devolatilization, polycondensation and carbonization reactions during torrefaction to form torrefied xylan with a condensed aromatic structure. The H/C or O/C ratio of torrefied xylan can be used as a structural indicator for quantitative evaluation of its torrefaction severity and resulting reactivity during pyrolysis and CO2 gasification. These findings can provide useful information for identifying the effect of torrefaction on structure alterations of hemicellulose and resulting reactivity during pyrolysis and CO2 gasification. Highlights: Quantitative structure-reactivity relationships of torrefied xylan were established. The pyrolysis/gasification reactivity of xylan was reduced by torrefaction. H/C ratio of xylan can be used for evaluation its pyrolysis/gasification reactivity.